Views and attitudes of healthcare professionals on do-not-attempt-cardiopulmonary-resuscitation in low-and-lower-middle-income countries: a systematic review - Mayank Gupta; Udita Joshi; Seema Rajesh Rao; Mirella Longo; Naveen Salins (BMC Palliative Care)
Abstract Background Healthcare Professionals (HCPs) are important stakeholders and gatekeepers in resuscitation decision-making. This systematic review explored the views and attitudes of HCPs on do-not-attempt-cardiopulmonary resuscitation (DNAR) in low-and-lower-middle-income countries (LLMICs). Methods PubMed, EMBASE, PsycInfo, CINAHL, Cochrane library, Scopus, and Web of Science were searched from 01-Jan-1990 to 24-February-2023. Empirical peer-reviewed literature exploring views and attitudes of HCPs on DNAR for adult patients (aged ≽18 years) in LLMIC were included. No restriction on empirical study designs was imposed. Two independent reviewers performed screening, data extraction and critical appraisal. Hawker’s tool and Popay’s narrative synthesis were used for critical appraisal and data synthesis respectively. Review findings were interpreted using Cognitive Dissonance theory (CDT). Results Of the 5132 records identified, 44 studies encompassing 7490 HCPs were included. The median Hawker score was 28 with 27% studies having low risk of bias. Three themes emerged. 1: Meaning-Making of DNAR construct. Most HCPs agreed that DNAR avoided inappropriate resuscitations, needless suffering and allowed fair allocation of resources. However, there was a lack of consensus on DNAR timing. 2: Barriers and Facilitators. Sociocultural norms, lack of legal clarity, organisational policies, societal and family views, religious and ethical beliefs, and healthcare providers’ presuppositions often hindered DNAR practice. HCPs had inconsistent religious and ethical beliefs about DNAR. 3: Tensions and complexities of contemporary practice. HCPs expressed fears, concerns, guilt and distress while recommending DNAR. HCPs differed on involving patients. The DNAR practice was arbitrary and suboptimal like informal DNAR orders, pretended and symbolic CPRs. Conclusion Most HCPs in LLMICs viewed DNAR as essential However, they faced barriers to DNAR implementation at macro-(law, sociocultural norms), meso-(organization) and micro-(HCP- and family views) levels. These barriers contributed to HCPs’ fears, concerns and distress concerning DNAR. The CDT provided the lens to link HCPs cognitions, affect and behaviour into a chain of events that explained suboptimal resuscitation practices. Trial registration CRD42023395887.